Purinergic signaling as a basis of acupuncture-induced analgesia - Jin-Rong He; Shu-Guang Yu; Yong Tang; Peter Illes (Purinergic Signalling, 2020)
This review summarizes experimental evidence indicating that purinergic mechanisms are causally involved in acupuncture (AP)-induced analgesia. Electroacupuncture (EAP) and manual AP release at pain-relevant acupoints ATP which may activate purinergic P2X receptors (Rs) especially of the P2X3 type situated at local sensory nerve endings (peripheral terminals of dorsal root ganglion [DRG] neurons); the central processes of these neurons are thought to inhibit via collaterals of ascending dorsal horn spinal cord neurons, pain-relevant pathways projecting to higher centers of the brain. In addition, during AP/EAP non-neuronal P2X4 and/or P2X7Rs localized at microglial cells of the CNS become activated at the spinal or supraspinal levels. In consequence, these microglia secrete bioactive compounds such as growth factors, cytokines, chemokines, reactive oxygen, and nitrogen species, which modulate the ascending neuronal pathways conducting painful stimuli. Alternatively, ATP released at acupoints by AP/EAP may be enzymatically degraded to adenosine, stimulating in loco presynaptic A1Rs exerting an inhibitory influence on the primary afferent fibers (the above mentioned pain-sensing peripheral terminals of DRG neurons) which thereby fail to conduct action potentials to the spinal cord dorsal horn. The net effect of the stimulation of P2X3, P2X4, P2X7, and A1Rs by the AP/EAP-induced release of ATP/adenosine at certain acupoints will be analgesia.